A Survey of Resources and Nursing Workforce for Clinical Research Delivery in Paediatric Intensive Care Within the UK / Ireland - Menzies, Julie C.; Jennings, Claire; Marshall, Rebecca (Frontiers in Pediatrics, 2022)
Introduction Clinical research within Paediatric Intensive Care (PICU) is necessary to reduce morbidity and mortality associated within this resource-intensive environment. With UK PICUs encouraged to be research-active there was a drive to understand how centres support research delivery. Aim To identify the research workforce available within UK/Ireland PICUs to support clinical research delivery. Method An electronic survey, endorsed by the Paediatric Critical Care Society (PCCS), was designed and reported in accordance with CHERRIES guidelines. The survey was distributed by email to all UK/Ireland Nurse Managers and Medical/ Nursing Research leads, aiming for one response per site during the period of April-June 2021. Only one response per site was included in analysis. Results 44 responses were received, representing 24/30 UK/Ireland sites (80% response rate). Responses from n=21/30 units are included (three excluded for insufficient data). 90% (n=19/21) units were research active, although only 52% (n=11) had permanent research roles funded within their staffing establishment. The majority of units (n=18, 86%) had less than two WTE research nurses. Resources were felt to be sufficient for current research delivery by 43% of units (n=9), but this confidence diminished to 19% (n=4) when considering their ability to support future research. The top barriers to research conduct were insufficiently funded/unfunded studies (52%; n=11), clinical staff too busy to support research activity (52%; n=11) and short-term/fixed-term contracts for research staff (38%; n=8). Conclusion Despite the perceived importance of research and 90% of responding UK/Ireland PICUs being research active, the majority have limited resources to support research delivery. This has implications for their ability to participate in future multi-centre trials and opportunities to support the development of future medical/nursing clinical academics. Further work is required to identify optimum models of clinical research delivery.